ZnTe layers on R ‐ and S ‐plane sapphire substrates. Issue 7 (9th February 2016) - Nakasu, Taizo; Hattori, Shota; Kizu, Takeru; Sun, Wei‐Che; Kazami, Fukino; Hashimoto, Yuki; Kobayashi, Masakazu; Asahi, Toshiaki
Abstract: ZnTe epilayers were grown on R ‐plane ( 10 1 4 ) and S ‐plane ( 10 1 1 ) sapphire substrates by molecular beam epitaxy, and the crystal orientation and the optical property were studied. The crystal orientation of ZnTe layers on sapphire substrates was studied using X‐ray diffraction pole figure measurements. It was confirmed that (111)‐oriented domains were formed on the R ‐plane as well as on the S ‐plane substrate. Layers grown on R ‐plane exhibited higher film quality. From the low‐temperature photoluminescence, emissions caused by ZnTe exciton were observed. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)